به دنبال تزریق خون در بیمارستان های شیراز ABO ارض ناسازگاری در سال 8931 لیلا. - لیلا کسرائیان; زهرا افسر; ابک شیرازی; مهتاب فرح انگیز; نیما نادری (Scientific Journal of Iranian Blood Transfusion Organization)
Background and Objectives One of the dangers of blood transfusions is the mistakes that lead to the wrong blood transfusion to the patient. This study was performed to identify the types of errors that lead to incompatible transfusions to prevent their recurrence and increase recipients health. Materials and Methods This cross-sectional study was performed on complications of ABO incompatibility caused by transfusion in 2019 in Shiraz hospitals. Demographic characteristics of blood recipients (age, sex, diagnosis, history of transfusion, blood type), type of product received, blood type of product received, incompatible blood volume injected, symptoms and causes of ABO incompatibility were determined. Chi-square and t-test were used to analyze data. Results A total of 9 complications of ABO incompatibility were reported; 7 cases (77.8%) were due to packed red blood cells, one case (11.1%) due to platelet injection and one (11.1%) due to plasma injection. Seven cases occurred in patients undergoing surgery, one case in neonates and one in thalassemia patients. In terms of clinical symptoms, only one patient developed chills. The rest of the patients had no symptoms. The most common error leading to inconsistency was the lack of accurate identification in 6 cases (66.7%) and in 2 cases (22.2%) sampling error and in one (11.1%) incorrect group writing. Conclusions It seems that in order to promote safe blood transfusion, it is important to investigate the occurrence of ABO incompatibilities in order to identify blood transfusion chain errors in order to identify the causes of errors and prevent the recurrence of these complications.